Differential Effectiveness of Tenofovir and Entecavir for Prophylaxis of Hepatocellular Carcinoma in Chronic Hepatitis B Patients Depending on Coexisting Cirrhosis and Prior Exposure to Antiviral Therapy: A Systematic Review and Meta-analysis. Issue 9 (October 2021) - Jeong, Seogsong; Cho, Yuri; Park, Sang Min; Kim, Won
Abstract : Goals: Thi s meta-analysis evaluated the comparative effectiveness of tenofovir disoproxil fumarate (TDF) versus entecavir (ETV) in reducing the risk of hepatocellular carcinoma (HCC). Background: It is unclear whether TDF or ETV is more effective in reducing the risk of HCC in chronic hepatitis B (CHB) patients with or without underlying cirrhosis. Methods: We searched the MEDLINE database through April 13, 2020, for studies involving CHB treated with TDF and/or ETV. Primary and secondary outcomes were the incidence of HCC and overall survival, respectively, calculated as risk ratios (RRs). Adjusted results were further evaluated by pooling propensity score matched cohorts. Results: Of the 229 records identified, 17 studies were included in the quantitative analysis. TDF treatment was associated with a significantly lower risk of HCC development [RR, 0.63; 95% confidence interval (CI), 0.43-0.93; P =0.024] and mortality (RR, 0.69; 95% CI, 0.57-0.84; P =0.003) than ETV treatment. Moreover, TDF significantly lowered HCC risk in patients with cirrhosis (RR, 0.69; 95% CI, 0.56-0.84) and antiviral treatment-naive patients (RR, 0.59; 95% CI, 0.35-0.98) compared with ETV. Among treatment-naive patients, TDF significantly prolonged survival compared with ETV (RR, 0.69; 95% CI, 0.52-0.91). Conclusions: TDF likely confers a lower risk of HCC development and longer survival in patients with CHB, especially among treatment-naive patients and those with underlying cirrhosis, than ETV. Abstract : Supplemental Digital Content is available in the text.